2017
DOI: 10.3389/fphar.2017.00675
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Cigarette Smoke-Induced Endoplasmic Reticulum Stress and Apoptosis in Bronchial Epithelial Cells

Abstract: Background: Apoptosis of lung structural cells contributes to the process of lung damage and remodeling in chronic obstructive pulmonary disease (COPD). Our previous studies demonstrated that exogenous hydrogen sulfide (H2S) can reduce the lung tissue pathology score, anti-inflammation and anti-oxidation effects in COPD, but the effect of H2S in regulating cigarette smoke (CS) induced bronchial epithelial cell apoptosis and the underlying mechanisms are not clear.Objectives: To investigate the effect of H2S on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…*p< 0.05, **p < 0.01, ***p < 0.001 between groups. PM 2.5 , fine particulate matter; Nrf2, nuclear factor erythroid 2 related factor 2. against cigarette smoke or ozone induced-COPD/emphysema, which further demonstrated that H 2 S was endogenous protection system in vivo and in vitro (Li F. et al, 2016;Lin et al, 2017). Though our study demonstrated that PM impaired endogenous H 2 S generation to cause lung damage, however, how PM decreased endogenous CTH expression level needs further study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…*p< 0.05, **p < 0.01, ***p < 0.001 between groups. PM 2.5 , fine particulate matter; Nrf2, nuclear factor erythroid 2 related factor 2. against cigarette smoke or ozone induced-COPD/emphysema, which further demonstrated that H 2 S was endogenous protection system in vivo and in vitro (Li F. et al, 2016;Lin et al, 2017). Though our study demonstrated that PM impaired endogenous H 2 S generation to cause lung damage, however, how PM decreased endogenous CTH expression level needs further study.…”
Section: Discussionmentioning
confidence: 53%
“…Our previous study showed that H 2 S was able to inhibit cigarette smoke-induced apoptosis in rat lung and bronchial epithelial cells (Lin et al, 2017). Its also reported that the activation of Nrf2 by bixin protected against PM 2.5 -induced lung injury by alleviating oxidative stress, increasing proliferation and migration, decreasing apoptosis (Zhang H. et al, 2018;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In mice, absence of CSE expression promotes AHR. 29 Exogenous administration of H 2 S has been demonstrated as protective in ventilator-induced lung injury, 68,69 acute lung injury, [70][71][72][73][74] hypoxia/hyperoxia environments, [74][75][76] and during acute viral illnesses. [77][78][79] Compared to these data, there is currently no information on H 2 S in the developing bronchial airways per se.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke (CS) induces ERS and ERS-mediated apoptosis and suppresses the production of endogenous H2S to lead COPD, which is reversed by exogenous H 2 S [83]. Intraperitoneal injection of endogenous H 2 S inhibitor in rat model of passive inhalation of CS aggravates these effects caused by CS; however, the ERS inhibitor suppresses CS-induced effects, which suggests that H 2 S may inhibit CS-induced bronchial epithelial cell apoptosis through suppressing ERS [84]. Artery endothelial dysfunction induced by apoptosis of arterial endothelial cells is associated with the severity of COPD [85].…”
Section: H 2 S Influences Endoplasmic Reticulum Stress In Respiratorymentioning
confidence: 99%